Photography, reconstruction and the cultural history of the postwar European city - Allbeson, Tom, author.
1 online resource
Keywords: "Examining imagery of urban space in Britain, France and West Germany up to the early 1960s, this book reveals how photography shaped individual architectural projects and national rebuilding efforts alike. Exploring the impact of urban photography at a pivotal moment in contemporary European architecture and culture, this book addresses case studies spanning the destruction of the war to the modernizing reconfiguration of city spaces, including ruin photobooks about bombed cities, architectural photography of housing projects and imagery of urban life from popular photomagazines, as well as internationally-renowned projects like UNESCO's Paris Headquarters, Coventry Cathedral and Berlin's Gedächtniskirche. This book reveals that the ways of seeing shaped in the postwar years by urban photography were a vital aspect of not only discourses on the postwar city, but also debates central to popular culture, from commemoration and modernization to democratization and Europeanization. This book will be fascinating reading for researchers in the fields of photography and visual studies, architectural and urban history, as well as cultural memory and contemporary European history"--